2013
DOI: 10.1177/0284185113491252
|View full text |Cite
|
Sign up to set email alerts
|

Can clinical and MRI findings predict the prognosis of variant and classical type of posterior reversible encephalopathy syndrome (PRES)?

Abstract: Even though BP influences the involvement of the brain stem, involvement of the brain stem is not influential on the prognosis. It seems that the influential factor to prognosis is the reversibility of lesions and hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 26 publications
(57 reference statements)
5
40
2
4
Order By: Relevance
“…Association of renal failure with PRES is present in 55% cases [7]. Prognosis of PRES is favourable, and most patients recover fully in about 75-90% cases [8] as seen clinically in both of our cases. There are three MRI patterns reported in 70% cases in radiology literature: a dominant parietooccipital pattern, holohemispheric watershed pattern and superior frontal sulcus pattern.…”
Section: Discussionsupporting
confidence: 57%
“…Association of renal failure with PRES is present in 55% cases [7]. Prognosis of PRES is favourable, and most patients recover fully in about 75-90% cases [8] as seen clinically in both of our cases. There are three MRI patterns reported in 70% cases in radiology literature: a dominant parietooccipital pattern, holohemispheric watershed pattern and superior frontal sulcus pattern.…”
Section: Discussionsupporting
confidence: 57%
“…10 Subarachnoid hemorrhage (SAH) is the most common type and the second most common is parenchymal hemorrhage in patients with PRES. 7,9 Our patient had both types of hemorrhage in the right temporal lobe. Findings of PRES on angiography include focal or diffuse vasoconstriction, vasodilation or a ''string-of-beads'' appearance.…”
Section: Resultsmentioning
confidence: 68%
“…The classical form is characterized by clinical symptoms that are associated with bilateral and symmetric vasogenic edema in the parietal and occipital lobes, while the variant form demonstrates predominant involvement of the brain stem and cerebellum. 6,7 A new definition, termed ''central variant,'' describes the form involving the central brainstem and basal ganglia but lacking cortical and subcortical oedema. 8 The patient in this report had a variant form where the pathologic process encompassed both the posterior and anterior circulations.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Reversibility of MRI findings is suggestive of a good prognosis. 16 Thus, leukoencephalopathy with severe hypertension is reversible both clinically and radiologically in the majority of children after the control of hypertension. 17 However, the literature has shown that a few patients may have residual damage and need to be followed-up.…”
Section: Discussionmentioning
confidence: 99%